Alternative Therapeutic Options to Antibiotics for the Treatment of Urinary Tract Infections - Loubet, Paul; Ranfaing, Jérémy; Dinh, Aurélien; Dunyach-Remy, Catherine; Bernard, Louis; Bruyère, Franck; Lavigne, Jean-Philippe; Sotto, Albert (Frontiers in Microbiology, 2020)
Urinary tract infections (UTIs) mainly caused by Uropathogenic Escherichia coli (UPEC), are common bacterial infections. Many individuals suffer from chronically recurring UTIs, sometimes requiring long-term prophylactic antibiotic regimens. The global emergence of multi-drug resistant uropathogens in the last decade underlines the need for alternative non-antibiotic therapeutic and preventative strategies against UTIs. The research on non-antibiotic therapeutic options in UTIs has focused on the following phases of the pathogenesis: colonization, adherence of pathogens to uroepithelial cell receptors and invasion. In this review, we discuss vaccines, small compounds, nutraceuticals, immunomodulating agents, probiotics and bacteriophages, highlighting the challenges each of these approaches face. Most of these treatments show interesting but only preliminary results. Lactobacillus-containing products and cranberry products in conjunction with propolis have shown the most robust results to date and appear to be the most promising new alternative to currently used antibiotics. Larger efficacy clinical trials as well as studies on the interplay between non-antibiotic therapies, uropathogens and the host immune system are warranted.